MRI of the Achilles tendon – a comprehensive pictorial review. Part two. (2021) - Szaro, Pawel; Nilsson-Helander, Katarina; Carmont, Michael
Highlights: The abnormalities on MRI should be correlated with the clinical findings. Higher signal of the Achilles tendon is a common postoperative finding. The fluid signal within the Achilles tendon graft indicates a rupture. Postoperative complications of Haglund's syndrome should be assessed on MRI. Elongation of the Achilles tendon is seen after surgical or conservative treatment. Abstract: The most common disorder affecting the Achilles tendon is midportion tendinopathy. A focal fluid signal indicates microtears, which may progress to partial and complete rupture. Assessment of Achilles tendon healing should be based on tendon morphology and tension rather than structural signal. After nonoperative management or surgical repair of the Achilles tendon, areas of fluid signal is pathologic because it indicates re-rupture. A higher signal in the postoperative Achilles tendon is a common finding and is present for a prolonged period following surgical intervention and needs to be interpreted alongside the clinical appearance.